A revision of Annularia and Asterophyllites species from the lower Westphalian (Middle Pennsylvanian) of the Maritime Provinces of Canada - Álvarez-Vázquez, Carmen; Wagner, Robert H. (Atlantic Geoscience, 2017)
As part of a larger project to revise the systematics of lower Westphalian floras of Nova Scotia and New Brunswick, the sphenopsid taxa are presently reviewed. We recognize 15 species, of which one, Annularia stopesiae, is new. Detailed synonymy lists allow a refinement of the stratigraphic and geographic ranges of these species. Scant attention has been paid previously to Canadian species in the European literature. For example, Annularia latifolia was described later from Europe as Annularia jongmansii. The identical composition of Westphalian floras from Canada and western Europe is striking.